Edukasi Kesehatan Reproduksi terhadap Remaja di SMA IT Ar-Rahman Banjarbaru - Nurul Hekmah; Nisa, Ainun; Fathullah, Desya Medinasari; Fajrina, Nur (UPPM Poltekkes Kemenkes Banjarmasin, 2023)
Teenagers are residents in the age range of 15-21 years. Physically, adolescent women need to be prepared in terms of knowledge regarding the beginning of pregnancy to birth. The nutritional problem that often arises in adolescents is the fulfillment of nutrition before marriage. Through the 1000 First Days of Life (HPK) movement, it is hoped that it can provide interventions to provide knowledge about pre-marital nutrition. Good nutritional status in expectant mothers during the preconception period is a determinant of the quality of human resources. Having good and proper knowledge about nutrition before marriage, as well as how to maintain their health, is expected to make teenagers more responsible. Educational activities are carried out by first asking questions to respondents before the implementation of education (pre-test) and returning questions after the implementation of education (post-test). The results of the educational activities showed that there was a change in adolescent knowledge regarding reproductive health, in this case regarding pre-marital nutrition, when viewed from the average scores obtained by students before and after the educational activities. The results achieved experienced an increase in knowledge as seen from the results of the pre test and post test. The increase in the percentage of students' knowledge before being given education by 52.1% increased to 78.5% after being given education. Educational activities regarding reproductive health like this are best given to teenage students and can be carried out periodically by school teachers to class X students in fulfilling the knowledge of adolescent students in preparation for entering the reproductive period.